2017
DOI: 10.1055/s-0037-1602584
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Decontamination with Antiseptics to Prevent Ventilator-Associated Pneumonia: Rethinking the Benefits of Chlorhexidine

Michael Klompas

Abstract: Daily oral care with chlorhexidine for mechanically ventilated patients is ubiquitous in contemporary intensive care practice. The practice is predicated upon meta-analyses suggesting that adding chlorhexidine to daily oral care regimens can reduce ventilator-associated pneumonia (VAP) rates by up to 40%. Close analysis, however, raises three concerns: (1) the meta-analyses are dominated by studies in cardiac surgery patients in whom average duration of mechanical ventilation is < 1 day and thus their risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 85 publications
0
31
0
9
Order By: Relevance
“…(weak recommendation, low quality of evidence) We recommend obtaining a lower respiratory tract sample (distal quantitative or proximal quantitative or qualitative culture) to focus and narrow the initial empiric antibiotic therapy. (strong recommendation, low quality of evidence) digestive decontamination may not be effective in ICUs with high baseline rates of antibiotic resistance, and subglottic secretion drainage may not shorten duration of mechanical ventilation or ICU length-of-stay as was once thought [91][92][93][94][95]. The practices most consistently associated with earlier extubation and/or lower mortality rates are those focused on limiting exposure to invasive mechanical ventilation by avoiding intubation and speeding extubation [96].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
See 1 more Smart Citation
“…(weak recommendation, low quality of evidence) We recommend obtaining a lower respiratory tract sample (distal quantitative or proximal quantitative or qualitative culture) to focus and narrow the initial empiric antibiotic therapy. (strong recommendation, low quality of evidence) digestive decontamination may not be effective in ICUs with high baseline rates of antibiotic resistance, and subglottic secretion drainage may not shorten duration of mechanical ventilation or ICU length-of-stay as was once thought [91][92][93][94][95]. The practices most consistently associated with earlier extubation and/or lower mortality rates are those focused on limiting exposure to invasive mechanical ventilation by avoiding intubation and speeding extubation [96].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…There is no association between oral care with chlorhexidine and lower VAP rates on meta-analysis of double-blind randomized trials [99]. More concerningly, some meta-analyses and observational studies have reported that oral care with chlorhexidine may increase mortality rates, perhaps because some patients may aspirate some of the antiseptic triggering acute lung injury [91,95,99,100,111,112]. A cluster randomized de-adoption study is currently underway to better characterize the safety and effectiveness of oral chlorhexidine for ventilated patients [113].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…Oral care with chlorhexidine has come under scrutiny in recent years because of a series of studies associating oral chlorhexidine with a possible increased risk of mortality and ventilator-associated events. 84 This signal has been noted on meta-analyses of randomized trials, 73,85 observational analyses of associations between ventilator bundle components and outcomes, 31,86,87 and in one hospital-wide observational analysis of prescribed medications. 88 In addition, doubt has been cast on whether oral care with chlorhexidine truly prevents VAP.…”
Section: Oral Care With Chlorhexidinementioning
confidence: 95%
“…Thus, modulation of orogastric colonization has been a central strategy in the prevention of VAP. Various concentrations of chlorhexidine, up to 2%, have been used to hinder oropharyngeal growth of pathogens [20], specifically in cardiac surgery ICU patients. Importantly, in recent years, arguments have been raised against the use of chlorhexidine, due to associated increased mortality.…”
Section: Pharmacological Measuresmentioning
confidence: 99%